Pelatihan Penyusunan Business Plan Bagi UMKM Kota Padang - Dika, Riri Putri; Sari, Vivi Puspita; Medina, Pinta (LPPM Universitas Dharma Andalas, 2025)
Entrepreneurship is one way for someone to work towards a career for their future life, besides that entrepreneurship also helps the government's task in reducing unemployment growth in this country. Opening a business or business is something that requires sincerity and maturity of steps. One form of sincerity that needs to be shown by someone who is an entrepreneur is to make a business plan. But unfortunately not everyone understands how to make a good and correct business plan. comprehensive understanding and able to influence a well-designed business and can form MSMEs to clarify the vision and mission, identify strengths, weaknesses, opportunities, and threats (SWOT analysis), develop strategies to utilize strengths, reduce weaknesses, take advantage of opportunities, and overcome threats (SWOT analysis), allocate resources effectively and efficiently, monitor progress and adjust strategies as Understanding the best strategies and practices of planning in entrepreneurship can provide significant benefits for MSMEs in the era of globalization. The involvement of human resources who understand the field makes the preparation of a business plan that is made only based on needs not a mature plan. To stay relevant and competitive with fellow MSMEs, it is important to think about a strategic and solid business plan, this is a management tool used to manage the current situation and project future conditions. A business plan is very important in guiding MSME business owners towards success.